The Strange Career of Independent Voting Trusts in U.S. Rail Mergers - Russell Pittman (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2016)
Voting trust arrangements have a long history at both the Interstate Commerce Commission and the Surface Transportation Board as devices to protect the incentives of acquiring firms and maintain the independence of acquiring and target firms during the pendency of regulatory investigation of the merger proposal
Keywords: 330